1997
DOI: 10.1046/j.1365-2125.1997.t01-1-00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of losartan on cerebral and ocular circulation in healthy subjects

Abstract: AimsThe introduction of specific inhibitors of AT 1 receptors, such as losartan, has enabled the investigation of the renin-angiotensin-system (RAS) in humans in vivo. We studied the role of the RAS in the cerebral and ocular circulation in healthy subjects. Haemodynamic effects of orally administered losartan were investigated with non-invasive methods. Methods In a placebo-controlled randomized, double-blind two way crossover design losartan (100 mg orally) or placebo was administered in 10 healthy subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
1
14
0
1
Order By: Relevance
“…Only a few previous studies have evaluated the effect of losartan on the brain in hypertensive patients. Matulla et al (9) indirectly suggested that losartan did not change the resting global cerebral blood flow in normal individuals, based on ultrasonography findings. This previous study measured blood flow velocities in the middle cerebral artery, not the cerebral blood flow, and only evaluated the acute effects of losartan.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have evaluated the effect of losartan on the brain in hypertensive patients. Matulla et al (9) indirectly suggested that losartan did not change the resting global cerebral blood flow in normal individuals, based on ultrasonography findings. This previous study measured blood flow velocities in the middle cerebral artery, not the cerebral blood flow, and only evaluated the acute effects of losartan.…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile fraction of blood flow in the OA was calculated as (MFVϪEDV)/MFV. 16,17 All parameters were determined as mean values over at least three cardiac cycles.…”
Section: Doppler Sonographymentioning
confidence: 99%
“…For example, ocular circulation is infl uenced by antihypertensive agents. 23,24 Another limitation of the present study is that we did not assess the infl uence of concomitant antihypertensive therapy, especially medications that alter the vascular tone, a topic that needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%